2021
DOI: 10.20525/ijfbs.v10i1.996
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Sustainability of Financial Intermediaries

Abstract: This paper provides interesting insights into the practices of banks and institutional setting in Sri Lanka. The sustainability and stability of banks that makes up an economy’s banking system should be sound at all time. This paper aimed at analyzing the determinants of banking sector stability in Sri Lanka. The study used a broad set of macro and bank level data covering 22 commercial banks for the period 1996-2016. The fixed effect GLS panel data model tested in this paper sets the relationship between bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Nguyen et al [4] discussed the influence of digital currency on the traditional banking system, and pointed out that the emergence of digital currency will promote the innovation of traditional banks in business model and risk management. Liyanagamage et al [5] analyzed the influence of digital currency on retail banking, and found that digital currency will have a far-reaching impact on retail banking, and promote the digitalization and intelligence of banking. Vives [6] studied the influence of digital currency on financial stability, and pointed out that the volatility of digital currency market had a certain threat to financial stability.…”
Section: Related Workmentioning
confidence: 99%
“…Nguyen et al [4] discussed the influence of digital currency on the traditional banking system, and pointed out that the emergence of digital currency will promote the innovation of traditional banks in business model and risk management. Liyanagamage et al [5] analyzed the influence of digital currency on retail banking, and found that digital currency will have a far-reaching impact on retail banking, and promote the digitalization and intelligence of banking. Vives [6] studied the influence of digital currency on financial stability, and pointed out that the volatility of digital currency market had a certain threat to financial stability.…”
Section: Related Workmentioning
confidence: 99%